Peran Allah dalam Penciptaan Manusia: Kajian Teologis Kitab Kejadian dan Relevansinya Masa Kini - Eva Maharani; Eunike Winny Pintaruan; Gisela Meri Kristina (Sabar : Jurnal Pendidikan Agama Kristen dan Katolik, 2025)
This study aims to explore in depth the role of God in the creation of humanity as depicted in the Book of Genesis and its relevance to contemporary Christian life. Using a qualitative method with a literature study approach, this research analyzes the texts of Genesis 1:26–28 and 2:7–8, supported by systematic theological perspectives from scholars such as Louis Berkhof and J. J. Davis. The findings reveal that God’s role is multidimensional: God as the Sovereign Designer, who initiates and perfectly orchestrates the creation process; the Personal Creator, who forms humans from the dust of the ground with purpose and intimacy; the Giver of Life, who breathes the breath of life into humanity; and the Mandate Giver, who delegates authority and responsibility to humans to govern His creation. This understanding has profound theological and ethical implications, particularly for the formation of Christian identity rooted in the image and likeness of God (imago Dei), the strengthening of ecological responsibility toward environmental stewardship, and the cultivation of a transformative spirituality centered on living out God’s will in daily life. Therefore, this study concludes that the doctrine of creation is not merely a historical truth but an existential foundation that guides the faith, morality, and practical life of believers in responding to contemporary spiritual and social challenges.